2022
DOI: 10.9758/cpn.2022.20.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dissociative Symptoms and Morning Cortisol Levels in Patients with Post-traumatic Stress Disorder

Abstract: Objective Patients with post-traumatic stress disorder (PTSD) showed inconsistencies in their cortisol level, an index of the hypothalamic-pituitary-adrenal axis function. This study examined the relationship between dissociation, childhood trauma, and morning cortisol levels in PTSD patients. Methods This study included 69 (23 males and 46 females) patients and 82 (22 males and 60 females) healthy controls (HCs). Clinical assessments, including the Childhood Trauma Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In general, during periods of stress, cortisol dysregulation can be identified, which produces volumetric alterations in the brain, so the two biomarkers have negative correlations in patients with PTSD [ 24 , 67 ]. How-ever, ironically, hypocortisolism was observed in patients with PTSD since it could be influenced by several causes including dissociative symptoms as we described [ 16 , 56 ,57]. Therefore, the relationship between cortisol and brain volume should be more discussed in further studies considering these points.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In general, during periods of stress, cortisol dysregulation can be identified, which produces volumetric alterations in the brain, so the two biomarkers have negative correlations in patients with PTSD [ 24 , 67 ]. How-ever, ironically, hypocortisolism was observed in patients with PTSD since it could be influenced by several causes including dissociative symptoms as we described [ 16 , 56 ,57]. Therefore, the relationship between cortisol and brain volume should be more discussed in further studies considering these points.…”
Section: Discussionmentioning
confidence: 78%
“…First, the characteristic of comparison group, sex, and comorbidity with other psychiatric disorder could account for the mixed finding. Second, dissociative symptom, which were commonly observed in patient with PTSD, could a significant influencing factor of low cortisol level in patients with PTSD [ 16 ]. Previous studies reported that the dissociative subtype of PTSD exhibit a symptom like derealization or depersonalization, which could be attributed to low cortisol levels of patients with PTSD [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Posttraumatic stress disorder (PTSD) is a common mental disorder consequence of exposure to traumatic events. Its symptoms consist of 4 major diagnostic clusters: intrusion/re-experiencing symptoms, avoidance symptoms, negative cognitions, symptoms of hyperarousal [ 1 , 2 ]. Psychotherapy and pharmacotherapy recommendations differ across PTSD treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%